Evidence of Horizontal Gene Transfer of 50S Ribosomal Genes rplB, rplD, and rplY in Neisseria gonorrhoeae - Manoharan-Basil, Sheeba Santhini; Laumen, Jolein Gyonne Elise; Van Dijck, Christophe; De Block, Tessa; De Baetselier, Irith; Kenyon, Chris (Frontiers in Microbiology, 2021)
Horizontal gene transfer (HGT) in the penA and multidrug efflux pump genes has been shown to play a key role in the genesis of antimicrobial resistance in Neisseria gonorrhoeae. In this study, we evaluated if there was evidence of HGT in the genes coding for the ribosomal proteins in the Neisseria genus. We did this in a collection of 11,659 isolates of Neisseria, including N. gonorrhoeae and commensal Neisseria species (N. cinerea, N. elongata, N. flavescens, N. mucosa, N. polysaccharea, and N. subflava). Comparative genomic analyses identified HGT events in three genes: rplB, rplD, and rplY coding for ribosomal proteins L2, L4 and L25, respectively. Recombination events were predicted in N. gonorrhoeae and N. cinerea, N. subflava, and N. lactamica were identified as likely progenitors. In total, 2,337, 2,355, and 1,127 isolates possessed L2, L4, and L25 HGT events. Strong associations were found between HGT in L2/L4 and the C2597T 23S rRNA mutation that confers reduced susceptibility to macrolides. Whilst previous studies have found evidence of HGT of entire genes coding for ribosomal proteins in other bacterial species, this is the first study to find evidence of HGT-mediated chimerization of ribosomal proteins.